Growth of poly(3, 4‐ethylenedioxythiophene) films prepared by base‐inhibited vapor phase polymerization. Issue 8 (6th February 2014) - Metsik, Jörgen; Saal, Kristjan; Mäeorg, Uno; Lõhmus, Rünno; Leinberg, Silver; Mändar, Hugo; Kodu, Margus; Timusk, Martin
ABSTRACT Transparent [90% transmittance at 550 nm at a sheet resistance (Rs) of 279 Ω sq−1] poly(3, 4‐ethylenedioxythiophene) (PEDOT) films with electrical conductivities up to 1354 S cm−1 are prepared using base‐inhibited vapor phase polymerization at atmospheric pressure. The influence of reaction conditions, such as temperature and growth time, on the film formation is investigated. A simple and convenient two‐electrode method is used for the in situ measurement of resistance, enabling to investigate the growth mechanism of polymer films and the influence of different parameters (relative humidity and the amount of oxidant) on the film growth. Low humidity exerts a detrimental effect on film growth and conductivity. In situ Rs measurements suggest that a large structural change occurs upon washing the PEDOT‐oxidant film. © 2014 Wiley Periodicals, Inc. J Polym Sci Part B: Polym. Phys. 2014, 52, 561–571